Aplication and comparison of univariate methods to evaluate the maize stability at Toluca-Atlacomulco Valley, Mexico - González, Andrés (2010)
The objective of this study was to apply 6 univariate methods to evaluate the stability of 25 maize (Zea mays L.) genotypes of Mexico’s highlands. The genotypes were evaluated in 4 environments, under a randomized complete block design, with 4 replications per environment. A combined analysis of variance with grain yield data was performed. The stability indexes calculated were Francis and Kannenberg’s standard deviation (Si) and coefficient of variation (CVi ), Eberhart and Russell’s stability parameters (bi and S2di), Wricke’s ecovalence (Wi ), Shukla’s stability variance (σi2 ), Huehn’s nonparametric measures (Si(1) and Si(2)), and Lin and Binns’ assessment of cultivar superiority (Pi). The results showed that almost all genotypes were classified as stable with 6 methods; Chalqueño, ETA 13, H-40, San Lucas, and VS-46E had lowest stability indexes. The biplot methodology identified these 5 genotypes, as well as Ixtlahuaca and HIT-3, as high yielding and stable varieties (from 5,92 to 7,91 t.ha-1). The biplot methodology also indicated that RG, bi, Pi y CVi were correlated,but they had little or no association with Si, Wi, σi2, Si(1), Si(2) and S2di indexes. Chalqueño and ETA 13 are Chalqueño race, Ixtlahuaca and San Lucas were identified as Cónico race, whereas and H-40, HIT 3, and VS-46E belong to other races, so these genotypes could be employed for increased the grain yield and the stability of maize in this region of Mexico.